2017
DOI: 10.1039/c6sm02623k
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin polymerization exhibits high mechano-geometric sensitivity

Abstract: How tension modulates cellular transport has become a topic of interest in the recent past. The effect of tension on clathrin assembly and vesicle growth continues to remain less understood. Here, we use the classical Helfrich theory to predict the energetic cost clathrin is required to pay to remodel membrane at different stages of vesicle formation. Our study reveals that this energetic cost is highly sensitive to not only the tension in the membrane but to the instantaneous geometry of the membrane during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…The requirement of actin dynamics to form a closed clathrin-coated bud shape in high-tension conditions provided support for two modeling studies that indicate that proteininduced snap-through instability can offset tension and drive CCP growth. 172,173 Further modeling revealed that energetic cost is sensitive to the geometry of membrane shape during vesicle formation 174 and confirmed experimental work that showed a reduction in CCP size at high tension. 171 Future modeling efforts should increasingly focus on multiscale approaches to integrate molecular dynamics simulation with continuum Monte-Carlo simulation to study proteinmembrane interactions in membrane trafficking processes.…”
Section: Computational Modelingsupporting
confidence: 69%
“…The requirement of actin dynamics to form a closed clathrin-coated bud shape in high-tension conditions provided support for two modeling studies that indicate that proteininduced snap-through instability can offset tension and drive CCP growth. 172,173 Further modeling revealed that energetic cost is sensitive to the geometry of membrane shape during vesicle formation 174 and confirmed experimental work that showed a reduction in CCP size at high tension. 171 Future modeling efforts should increasingly focus on multiscale approaches to integrate molecular dynamics simulation with continuum Monte-Carlo simulation to study proteinmembrane interactions in membrane trafficking processes.…”
Section: Computational Modelingsupporting
confidence: 69%
“…Together, our analysis provides clear evidence that fMLP stimulation promotes nucleation of CCP and suggests the endocytic machineries signal to actin polymerization in neutrophil polarization. The observation of smaller CCPs is consistent with previous findings that cells with high tension have smaller CCPs [ 34 , 35 ] where we expect the leading edge of the cell to have higher membrane tension [36] . Previous work has demonstrated that receptor clustering can promote CCP nucleation [13] .…”
Section: Resultssupporting
confidence: 92%
“…The requirement for two distinct mechanisms in two regions of neck radii could be related to the energy barrier that we found as the neck radius of the catenoid decreases. Other evidence of switch-like behaviors are found in endocytosis where multiple studies have reported the existence of a snap-through instability 35,[64][65][66] . Furthermore, soap films, with no bending rigidity, also exhibit a structural instability when held as catenoids 45,67 .…”
Section: Discussionmentioning
confidence: 98%